Common Tangent Mania

Calculus Level pending

Let e e be Euler's number and a a and b b be real numbers and x > 1 |x| > 1 .

Let f ( x ) = lim n j = 1 n ( 1 x ) j j = 1 n ( j n ) n ( 1 x ) n j f(x) = \lim_{n \rightarrow \infty} \dfrac{\sum_{j = 1}^{n} (\dfrac{1}{x})^{j}}{\sum_{j = 1}^{n} (\dfrac{j}{n})^n (\dfrac{1}{x})^{n - j}} and g ( x ) = a x 2 + b x g(x) = ax^2 + bx .

If f ( x ) f(x) and g ( x ) g(x) have a common tangent at x = e x = e , find the value of a + b a + b to seven decimal places.


The answer is 0.4689487.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Jun 15, 2018

Let x > 1 |x| > 1 .

lim n j = 1 n ( j n ) n ( 1 x ) n j = \lim_{n \rightarrow \infty} \sum_{j = 1}^{n} (\dfrac{j}{n})^n (\dfrac{1}{x})^{n - j} = lim n j = 0 n 1 ( 1 j n ) n ( 1 x ) j = \lim_{n \rightarrow \infty} \sum_{j = 0}^{n - 1} (1 - \dfrac{j}{n})^n (\dfrac{1}{x})^{j} = j = 0 ( 1 e x ) j = e x e x 1 \sum_{j = 0}^{\infty} (\dfrac{1}{ex})^j = \dfrac{ex}{ex - 1} on x > 1 e |x| > \dfrac{1}{e}

f ( x ) = lim n j = 1 n ( 1 x ) j j = 1 n ( j n ) n ( 1 x ) n j = e x 1 e x ( x 1 ) \implies f(x) = \lim_{n \rightarrow \infty} \dfrac{\sum_{j = 1}^{n} (\dfrac{1}{x})^{j}}{\sum_{j = 1}^{n} (\dfrac{j}{n})^n (\dfrac{1}{x})^{n - j}} = \dfrac{ex - 1}{ex(x - 1)} .on x > 1 |x| > 1 .

f ( e ) = g ( e ) e 2 a + e b = e + 1 e 2 e a + b = e + 1 e 3 f(e) = g(e) \implies e^2a + eb = \dfrac{e + 1}{e^2} \implies \boxed{ea + b = \dfrac{e + 1}{e^3}}

d d x ( f ( x ) ) = e x 2 2 x + 1 e x 2 ( x 1 ) 2 \dfrac{d}{dx}(f(x)) = -\dfrac{ex^2 - 2x + 1}{ex^2(x - 1)^2} \implies d d x ( f ( x ) ) x = e = e 2 + e 1 e 3 ( e 1 ) = d d x ( g ( x ) ) x = e = ( 2 e ) a + b \dfrac{d}{dx}(f(x))|_{x = e} = -\dfrac{e^2 + e - 1}{e^3(e - 1)} = \dfrac{d}{dx}(g(x))|_{x = e} = (2e)a + b \implies

( 2 e ) a + b = e 2 + e 1 e 3 ( e 1 ) \boxed{(2e)a + b = -\dfrac{e^2 + e - 1}{e^3(e - 1)}}

e a + b = e + 1 e 3 \boxed{ea + b = \dfrac{e + 1}{e^3}}

Solving the system we obtain:

a = 2 e 2 e + 2 e 4 ( e 1 ) a = \dfrac{-2e^2 - e + 2}{e^4(e - 1)} and b = 3 e 2 + e 3 e 3 ( e 1 ) b = \dfrac{3e^2 + e - 3}{e^3(e - 1)}

a + b = 3 e 2 + 2 e 2 e 4 0.4689487 \implies a + b = \dfrac{3e^2 + 2e - 2}{e^4} \approx \boxed{0.4689487} .

Note: The common tangent line is: ( e 2 + e 1 ) x + e 3 ( e 1 ) y e ( 2 e 2 + e 2 ) = 0 (e^2 + e - 1)x + e^3(e - 1)y - e(2e^2 + e - 2) = 0 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...